Fertilization increases soil organic carbon stocks but does not mitigate climate change in the Argentine Pampas - Alvarez, Roberto (2023)
Soils can act as carbon sinks mitigating global warming. This generates interest in determining how agricultural practices affect the stock of soil organic carbon (SOC). Fertilization increases SOC stocks and its impacts have been calculated at a global level. The aim of this study was to determine if fertilization leads to carbon sequestration in the Pampas of Argentina. A meta-analysis of local studies was performed to determine how fertilization impacts SOC stocks in agricultural soils. Forty studies were compiled presenting data from 27 experiments from which 109 comparisons of SOC stocks between fertilized and unfertilized treatments were extracted. Fertilization caused a significant increase of ca. 3% in the topsoil (0-20 cm) SOC stock. When nutrients application rate could be accurately defined (n= 71), the average increase in SOC stock was ca. 1 t ha-1. Increments were much smaller in comparison with those reported in literature and the carbon footprint of applied nutrients (2.31 t Ceq. ha-1). Even if increments in SOC stock in the subsoil were similar to those measured in the topsoil, greenhouse gas emission from fertilizer application would not be offset by the carbon sequestered in the soil. Fertilization has a low impact on SOC stocks and does not compensate greenhouse gases emissions in the Pampas. Rates of SOC increments resulting from fertilization identified in other regions of the world should not be applied in this region.